STUDY ON IMPACT OF EXECUTION OF LBA, 2015 ON THE ERSTWHILE ENCLAVES’ PEOPLE OF INDIA AND BANGLADESH - Bhattacharya, Debarshi (PEOPLE: International Journal of Social Sciences, 2018)
Enclaves in India and Bangladesh were dire outcome of historical partition of India in 1947. Inhabitants within enclaves of both the countries were forced to live in ‘no-man’s land’ as ‘nowhere people’ till 67 years after India’s independence and partition. They were discriminatorily deprived from getting basic amenities, rights, opportunities and governmental supports until signing of the historic Land Boundary Agreement (LBA) between India and Bangladesh in 2015. As per LBA, 2015, 51 Bangladeshi enclaves inside India and 111 Indian enclaves inside Bangladesh were actually transferred to each other w.e.f. July 31, 2015 midnight. A study was undertaken through extensive field survey in various erstwhile enclaves of both the countries to assess real impact of LBA, 2015 on the status of erstwhile enclaves’ people. During said study, entire population of these enclaves cordially welcomed exchange of enclaves through LBA, 2015, as they got rid of their exiled life of long 67 years by means of LBA, 2015. But even after execution of LBA, 2015, major problematic issues in these erstwhile enclaves had not yet been resolved; nor had rehabilitation packages so far been implemented for them.